2012
DOI: 10.1016/j.jtcvs.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of dehiscence after tricuspid valve repair with rigid annuloplasty rings

Abstract: Although both rigid and flexible systems provide acceptable early tricuspid valve repair results, use of a rigid ring increases risk of subsequent ring dehiscence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 17 publications
3
65
2
3
Order By: Relevance
“…Navia et al (12) and Izutani et al (13) reported a lower rate of recurrent TR with a rigid annuloplasty ring compared with a flexible ring. On the contrast, Pfannmüller et al (14) reported a higher rate of annuloplasty dehiscence after the implantation of a rigid ring. In the present study, the purpose was to compare the efficacy and mid-term durability of tricuspid ring annuloplasty for FTR secondary to rheumatic mitral valve disease using Cosgrove-Edwards flexible band and the Edwards MC3 rigid ring (Edwards Lifesciences, LLC, Irvine, CA, USA).…”
Section: Original Articlementioning
confidence: 94%
See 2 more Smart Citations
“…Navia et al (12) and Izutani et al (13) reported a lower rate of recurrent TR with a rigid annuloplasty ring compared with a flexible ring. On the contrast, Pfannmüller et al (14) reported a higher rate of annuloplasty dehiscence after the implantation of a rigid ring. In the present study, the purpose was to compare the efficacy and mid-term durability of tricuspid ring annuloplasty for FTR secondary to rheumatic mitral valve disease using Cosgrove-Edwards flexible band and the Edwards MC3 rigid ring (Edwards Lifesciences, LLC, Irvine, CA, USA).…”
Section: Original Articlementioning
confidence: 94%
“…Recently, valve annuloplasty is the preferred surgical treatment for FTR (17)(18)(19). However, to date there is no clear evidence of the superiority of one annuloplasty device over the other (14,19). To our knowledge, this is the first report explored and compared the efficacy and midterm outcomes of the tricuspid ring annuloplasty for FTR secondary to rheumatic mitral valve disease using flexible band and rigid ring.…”
Section: Mortality and Follow Upmentioning
confidence: 97%
See 1 more Smart Citation
“…Tricuspid annuloplasty (TA) is currently recommended for the treatment of significant TR3, 4 and has been increasingly performed over the past decade 5. Although TA has shown a satisfactory outcome in the short term, postoperative residual significant TR and mortality remain high during long‐term follow‐up 6, 7. Accurate preoperative risk evaluation is essential to identify patients at high risk and improve clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated in our experience that bands are more favorable compared to rigid rings in the tricuspid position (7). Annuloplasty sutures are placed in a routine fashion, avoiding any interference with the myocardial conduction system.…”
Section: Tv Repairmentioning
confidence: 82%